Erythorbyl laurate as a potential food additive with multi-functionalities: Antibacterial activity and mode of action. (April 2018) - Park, Kyung-Min; Jo, Su-Kyung; Yu, Hyunjong; Park, Jun-Young; Choi, Seung Jun; Lee, Chang Joo; Chang, Pahn-Shick
Abstract: The antibacterial activity and mechanism of erythorbyl laurate were investigated to provide information on practical applications as a multi-functional food additive. Antibacterial susceptibility screening demonstrated that erythorbyl laurate exerted both bacteriostatic and bactericidal effects on gram-positive foodborne pathogens (minimum inhibitory concentration: 0.48–0.88 mM, minimum bactericidal concentration: 0.65–1.00 mM). The growth curves of gram-positive strains showed increases in the λ (lag phase) accompanied by decreases in the μmax (maximum specific growth rate) as the concentration of erythorbyl laurate increased. The results of the crystal violet uptake and LIVE/DEAD Bac Light assays suggested that the antibacterial mechanism of erythorbyl laurate might depend on alterations in the permeability and integrity of cell membranes. Furthermore, erythorbyl laurate showed strong synergistic effects when combined with a variety of antibacterial agents including nisin, kanamycin, and erythromycin (FIC index < 0.28), which might result from increases in bacterial membrane permeability induced by erythorbyl laurate. Graphical abstract: Highlights: Erythorbyl laurate (EL) is a promising candidate for a multi-functional food additive. EL had bactericidal and bacteriostatic effects on gram-positive foodborne pathogens. Primary target of EL was the alteration in permeability and integrity of cell membranes. EL showed synergistic effects when combined with divers antibacterial agents.